Pengaruh Lingkungan Kerja, Gaya Kepemimpinan dan Religiusitas Terhadap Produktivitas Karyawan PT. Nada Surya Tunggal Melalui Kepuasan Kerja - Wijaya, Rendra; Bahjatulloh, Qi Mangku (Faculty of Islamic Economics and Business, Madura Islamic State University, 2022)
Purpose from this study is analyze the effect of the work environment, leadership style, and religious attitudes on employee productivity through job satisfaction as a mediating variable. The data in this study were obtained from a questionnaire that had been circulated and then tested using SPSS V25. The sample of this research are employees of PT. Nada Surya Tunggal has 110 employees. From the data analysis that has been carried out, it shows that: (1) Work environment has a significant positive effect on work productivity (2) Leadership style has a significant positive effect on work productivity (3) Religiosity has a significant positive effect on work productivity (4) Work environment has a positive effect significant positive effect on job satisfaction (5) Leadership style has a significant positive effect on work productivity (6) Religiosity has a positive and insignificant effect on work productivity (7) Job satisfaction has a significant positive effect on work productivity. (8) Job satisfaction is able to mediate the relationship between the work environment and work productivity (8) Job satisfaction is able to mediate the relationship between leadership style and work productivity (10) Job satisfaction is able to mediate the relationship between religiosity and employee productivity.